Understanding civic commitment amongst Singaporean youth as a collective whole - Koh, Kai Ting (Nanyang Technological University, 2024)
The Singapore Perspective forum, the annual flagship conference organized by the Institute of Policy Studies (IPS), centered around the theme “Youth” in this year’s 24th edition. It identified the youth segment as a public policy point of discussion. The role of young people in civic participation and fostering democratic values is increasingly recognized as pivotal. Yet concerning national stakeholders is the popularized view that the younger generation of Singaporeans are disengaged from civic affairs. Much scholarship on civic commitment and youth centers around the types of civic commitment or the individual differences in civic commitment. This research will attempt to identify cohort-wide trends in and factors informing civic engagement among Singaporean youth in recent years through consolidation of news articles, grey literature and academic publishing concerning this topic. It is supplemented by individual and layman sentiments from semi-formal interviews conducted for 18 Singaporean young adults ages ranging between 21-24 as of 1st January 2024. Examining demographic-wide trends and influences rather than discrete individual ones would serve to identify the shared experiences and contextual factors that underly youth’s relationship with civic commitment. These would provide policymakers, educators, and stakeholders a better understanding of the civic inclinations of young adults as a collective whole and hence provide a solid foundation for strategy-design to promote active citizenship among youths, thereby fostering a more inclusive and democratic society.